2017
DOI: 10.1097/ico.0000000000001316
|View full text |Cite
|
Sign up to set email alerts
|

Self-Retained Amniotic Membrane Combined With Antiviral Therapy for Herpetic Epithelial Keratitis

Abstract: PURPOSE To evaluate the therapeutic benefit of self-retained cryopreserved amniotic membrane (CAM) in conjunction with oral antiviral therapy in herpetic epithelial keratitis. METHODS Retrospective review of 4 patients with primary (1 eye) and recurrent (3 eyes) unilateral herpetic epithelial keratitis treated with CAM through the placement of PROKERA® Slim (Bio-Tissue, Miami, FL) (PKS) in conjunction with oral acyclovir. Their symptoms, conjunctival inflammation, corneal staining, and visual acuity were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Overall, these findings support the use of AM in promoting complete epithelialization of corneal ulcers caused by underlying NK. Three retrospective case series [15][16][17] have reported findings regarding the use of self-retained cAM for the treatment of corneal ulcers. Cheng and Tseng found 4 herpetic corneal ulcers underwent rapid corneal epithelization within 5 ± 4 days of PKS placement along with reduced ocular surface inflammation and improved VA during 3-51 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, these findings support the use of AM in promoting complete epithelialization of corneal ulcers caused by underlying NK. Three retrospective case series [15][16][17] have reported findings regarding the use of self-retained cAM for the treatment of corneal ulcers. Cheng and Tseng found 4 herpetic corneal ulcers underwent rapid corneal epithelization within 5 ± 4 days of PKS placement along with reduced ocular surface inflammation and improved VA during 3-51 months of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng and Tseng found 4 herpetic corneal ulcers underwent rapid corneal epithelization within 5 ± 4 days of PKS placement along with reduced ocular surface inflammation and improved VA during 3-51 months of follow-up. 16 In another short-term study, Suri et al described how 73% (8/11) of corneal ulcers healed following PROKERA ® placement despite failure to heal with prior use of punctal plugs (n = 5), BCL (n = 4), and tarsorrhaphy (n = 2); 15 remarkably, one eye with descemetocele re-epithelialized and formed an anterior chamber following treatment with PROKERA ® despite failure to heal with BCL. 15 In a case series involving corneal ulcers with bacterial keratitis, Sheha et al found 2 of 3 corneal ulcers healed in 14 and 23 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amniotic membrane has anti-inflammatory effects on activated neutrophils, lymphocytes and macrophages, reduces levels of inflammatory cytokines, IL-2 and IFN-γ, and may release nerve growth factor, allowing for improved wound healing. 132…”
Section: Treatment Approachesmentioning
confidence: 99%
“…Of these choices, AM not only delivers steroid-sparing anti-inflammatory, anti-scarring, and pro-regenerative properties 2,3 but also provides a mechanical protective barrier effect. Suture of cryopreserved AM in the operating room [4][5][6] or placement of self-retained cryopreserved AM in-office [7][8][9][10] has successfully treated corneal ulcers of various etiologies. However, comparative analysis between self-retained AM and a control group has not been performed.…”
mentioning
confidence: 99%